Beyond policy: perspectives of school health practitioners about providing contraception services to school-going adolescents in South Africa - Thabile J. Ketye; Gbotemi Bukola Babatunde; Olagoke Akintola (BMC, 2024)
Abstract Background Providing contraception to adolescents is a critical intervention in reducing adolescent and early pregnancy. However, many adolescents, including those attending school, still lack access to contraception. We adapted Baroudi's ecological framework of access to healthcare to explore the perspectives of school health practitioners about providing contraceptive services to school-going adolescents. Methods This is an exploratory qualitative research study. We employed purposive sampling to recruit school health practitioners directly involved in implementing sexual and reproductive health policies or interventions in public secondary schools. From September to October 2023, we conducted semi-structured interviews with forty-nine participants. We followed Braun and Clarke's approach of thematic analysis and adhered to the Consolidated Criteria for Reporting Qualitative Studies checklist for qualitative research reporting. Results In our study, participants highlighted the importance of having access to accurate information about contraception and being knowledgeable about school health policies. They also identified socio-cultural norms, denialism and misconceptions as potential barriers to contraception access. Notably, they suggested that strengthened parental involvement and the presence of nurses in schools could significantly improve the provision of contraceptive services to school-going adolescents. Conclusions Our study offers valuable insights into the perspectives of school health practitioners about providing contraception to adolescents. These findings highlight the implications of implementing the Integrated School Health Policy and the Policy on the prevention and management of learner pregnancy in schools. The results of this study could provide valuable insights to policymakers, decision-makers, nurses, and teachers from the Departments of Education and Health. Those insights could enhance the development of school health policies and the implementation of contraception-related programmes for adolescents in secondary schools. This, in turn, would contribute to reducing adolescent pregnancies in South Africa.